2017
DOI: 10.3390/rs9111142
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Improvements of GPM Dual-Frequency Precipitation Radar (DPR) upon TRMM Precipitation Radar (PR) in Global Precipitation Rate Estimation, Type Classification and Vertical Profiling

Abstract: Spaceborne precipitation radars are powerful tools used to acquire adequate and highquality precipitation estimates with high spatial resolution for a variety of applications in hydrological research. The Global Precipitation Measurement (GPM) mission, which deployed the first spaceborne Ka-and Ku-dual frequency radar (DPR), was launched in February 2014 as the upgraded successor of the Tropical Rainfall Measuring Mission (TRMM). This study matches the swath data of TRMM PR and GPM DPR Level 2 products during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 75 publications
2
29
0
Order By: Relevance
“…Compared to IR, MW provides more direct and accurate precipitation measurements because of its sensitivity to rain/ice particles, whereas IR‐based algorithms are often built on empirical and indirect links between cloud top brightness temperature ( T b ) and surface precipitation (Huffman et al, ; Kidd et al, ; Sorooshian et al, ). Active microwave sensors, that is, spaceborne radars, often provide more direct and accurate precipitation estimates than passive microwave (PMW) sensors (Behrangi et al, ; Gao et al, ; Tang et al, ; Tang, Long, et al, ). So far, there have been three popular spaceborne radars for observing precipitation, that is, the Ku‐band precipitation radar onboard the Tropical Rainfall Measuring Mission (TRMM) satellite operating from 1997 to 2015, the W‐band Cloud Profiling Radar (CPR) onboard the CloudSat operating from 2006 to the present, and the Dual‐frequency Precipitation Radar (DPR) onboard the Global Precipitation Measurement (GPM) Core Observatory operating from 2014 to the present.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to IR, MW provides more direct and accurate precipitation measurements because of its sensitivity to rain/ice particles, whereas IR‐based algorithms are often built on empirical and indirect links between cloud top brightness temperature ( T b ) and surface precipitation (Huffman et al, ; Kidd et al, ; Sorooshian et al, ). Active microwave sensors, that is, spaceborne radars, often provide more direct and accurate precipitation estimates than passive microwave (PMW) sensors (Behrangi et al, ; Gao et al, ; Tang et al, ; Tang, Long, et al, ). So far, there have been three popular spaceborne radars for observing precipitation, that is, the Ku‐band precipitation radar onboard the Tropical Rainfall Measuring Mission (TRMM) satellite operating from 1997 to 2015, the W‐band Cloud Profiling Radar (CPR) onboard the CloudSat operating from 2006 to the present, and the Dual‐frequency Precipitation Radar (DPR) onboard the Global Precipitation Measurement (GPM) Core Observatory operating from 2014 to the present.…”
Section: Introductionmentioning
confidence: 99%
“…However, there could be errors of the classification results due to some limitations of PR including low sensitivity for light rain and snow, single-frequency detection at Ku-band, and the coarse horizontal resolution above the ground. This problem has already been noticed [159,160], and could be improved by future algorithms and the next-generation space-borne precipitation radar [161][162][163][164].…”
Section: Errors and Limitations Of The Pr Datamentioning
confidence: 91%
“…Tian et al (2018) demonstrated that GPM rain retrievals generally overestimated light rainfall events and underestimated heavy events over land. In spite of this, studies indicate that GPM is more accurate than TRMM when determining whether precipitation is occurring (Gao et al 2017) and light precipitation rates over complex terrain (Ma et al 2016). In one study over the Swiss Alps using surface radars and rain gauges, Speirs et al (2017) showed that GPM retrievals generally underestimate precipitation during the winter, being most accurate when liquid-phase precipitation is occurring.…”
Section: B Gpm Datamentioning
confidence: 99%